Clinical Approach to Hypocalcemia in Newborn Period and Infancy: Who Should Be Treated?. (19th June 2019) - Vuralli, Dogus
Abstract : Introduction . Hypocalcemia is a common metabolic problem in newborn period and infancy. There is consensus on the treatment of the symptomatic cases while the calcium level at which the treatment will be initiated and the treatment options are still controversial in asymptomatic hypocalcemia. Methods . This review article will cover hypocalcemia with specific reference to calcium homeostasis and definition, etiology, diagnosis, and treatment of hypocalcemia in newborn and infancy period. Results . Hypocalcemia is defined as total serum calcium <8 mg/dL (2 mmol/L) or ionized calcium <4.4 mg/dL (1.1 mmol/L) for term infants or preterm infants weighing >1500 g at birth and total serum calcium <7 mg/dL (1.75 mmol/L) or ionized calcium <4 mg/dL (1 mmol/L) for very low birth weight infants weighing <1500 g. Early-onset hypocalcemia is generally asymptomatic; therefore, screening for hypocalcemia at the 24th and 48th hour after birth is warranted for infants with high risk of developing hypocalcemia. Late-onset hypocalcemia, which is generally symptomatic, develops after the first 72 h and toward the end of the first week of life. Excessive phosphate intake, hypomagnesemia, hypoparathyroidism, and vitamin D deficiency are commonest causes of late-onset hypocalcemia. Hypocalcemia should be treated according to etiology. Calcium replacement is the cornerstone of the treatment. Elementary calcium replacement of 40 to 80 mg/kg/d is recommended for asymptomatic newborns. Elementary calcium of 10 to 20 mg/kg (1–2 mL/kg/dose 10% calcium gluconate) is given as a slow intravenous infusion in the acute treatment of hypocalcemia in patients with symptoms of tetany or hypocalcemic convulsion. Conclusion . Since most infants with hypocalcemia are usually asymptomatic, serum total or ionized calcium levels must be monitored in preterm infants with a gestational age <32 weeks, small for gestational age infants, infants of diabetic mothers, and infants with severe prenatal asphyxia with a 1 min Apgar score of <4. The treatment of hypocalcemia should be initiated immediately in infants with reduced calcium levels while investigating the etiology.